2020
DOI: 10.1158/1055-9965.epi-19-0906
|View full text |Cite
|
Sign up to set email alerts
|

Using Continuous Glucose Monitoring to Motivate Physical Activity in Overweight and Obese Adults: A Pilot Study

Abstract: Background: Regular physical activity (PA) is associated with a lower risk of several types of cancers. However, two-thirds of overweight/obese adults are not sufficiently active; this, in combination with the unfavorable effect of excess body weight, puts them at a greater risk for cancer. One reason that these individuals do not engage in enough PA may be their lack of motivation to change their current behavior due to the perception of putting in effort for possible future gain without obvious short-term be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
(32 reference statements)
0
25
0
1
Order By: Relevance
“…Several participants discussed increasing their physical activity, interrupting sitting time and making changes to when and what food was consumed. This may be in part because participants found the glucose feedback motivating to make changes [ 33 , 34 ]. It could also be because the two devices provided feedback that was actionable and continuously available [ 35 ] and offered information on the health consequences of behaviour [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several participants discussed increasing their physical activity, interrupting sitting time and making changes to when and what food was consumed. This may be in part because participants found the glucose feedback motivating to make changes [ 33 , 34 ]. It could also be because the two devices provided feedback that was actionable and continuously available [ 35 ] and offered information on the health consequences of behaviour [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that GGE may act through the Health Belief Model; wherein, people experience a change in perceived risk by associating their dietary intake to health risk outcomes. Future research will be needed to understand and leverage the use of biological feedback as a cancer prevention strategy better [54].…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial hyperglycemia was shown to be associated with cardiovascular diseases [54]. The direct feedback and visualization of success (positive effect of physical activity on glucose dynamics) may be a motivating factor for increasing regular physical activity [60,61]. Bailey et al [60] evaluated the efficacy of an 8-week exercise program using CGM compared to a standard exercise program in terms of exercise adherence among individuals with impaired glucose tolerance (n = 13).…”
Section: Physical Activitymentioning
confidence: 99%
“…Although both groups improved their health-related quality of life, waist circumference, and fitness, the CGM group showed significantly higher increases in program attendance and registration rates for additional exercise programs than the control group. In the investigation by Liao et al [61], CGM systems were used in combination with fitness trackers in healthy, nondiabetic, overweight subjects (n = 19) during a free-living 10-day period to assess their influence on exercise motivation and physical activity. The results of the study indicated that the use of CGM systems (in combination with a fitness tracker) can support users in transitioning from the precontemplation stage (no intention of changing behavior) to the action stage (changing behavior).…”
Section: Physical Activitymentioning
confidence: 99%